2017
DOI: 10.1002/ams2.271
|View full text |Cite
|
Sign up to set email alerts
|

Do not attempt resuscitation order in Japan

Abstract: AimIn Japan, the do not attempt resuscitation (DNAR) order is practised routinely even though no related laws or guidelines exist. This study aimed to clarify the current status of DNAR, reveal existing DNAR‐related issues, and improve the application of DNAR.MethodsA questionnaire survey of medical institutions in Kanagawa Prefecture (total population, 9,120,000) about the current status of DNAR was carried out.ResultsThe results showed that DNAR has been practised at approximately 90% of the hospitals survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…4 There are no universally accepted protocols, laws, or evidence-based guidelines in regard to the procedure of ascertaining do not attempt cardiopulmonary resuscitation (DNACPR) in Japan. 5 Commonly, DNACPR is provided by the patient to the treating physician, sometimes with an aid of other healthcare personnel such as nurses, and it can also be given by the family member, but there is no standard process accepted to all for the reason described above. Therefore, when acutely ill patients are hospitalized, early decision-making regarding whether or not to have DNACPR order can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…4 There are no universally accepted protocols, laws, or evidence-based guidelines in regard to the procedure of ascertaining do not attempt cardiopulmonary resuscitation (DNACPR) in Japan. 5 Commonly, DNACPR is provided by the patient to the treating physician, sometimes with an aid of other healthcare personnel such as nurses, and it can also be given by the family member, but there is no standard process accepted to all for the reason described above. Therefore, when acutely ill patients are hospitalized, early decision-making regarding whether or not to have DNACPR order can be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, DNAR causes confusion between paramedics and family members, and instructions from physicians are necessary during emergency in Japan. 13 Nakagawa et al 14 reported that most hospitals have experienced patients with DNARs, yet not many hospitals have a guideline for DNARs. When patients with DNARs go into CPA at their home, it is unclear whether CPR should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the ideal way of language should be determined for community norms to share DNAR with patients/relatives. The most important determinants in DNAR decision are found to be prognosis of the disease and expected life quality (12). The most DNAR requests belong to malignant tumors, dementia, cerebrovascular disease sequels (13).…”
Section: Discussionmentioning
confidence: 99%